ANALYSIS OF PROCESS INTENSIFICATION METHODS IN SHELL TUBE HEAT EXCHANGERS - B.J. Khursanov (Modern American Journals, 2025)
The article describes the problems of heat exchange processes and devices and their solutions. Methods of intensification of processes in shell and tube heat exchangers are analyzed. Different turbulizers are used to speed up heat exchange. Turbulizers make the boundary layer of the heat-carrying medium on the surface of the pipes into a vortex or absorb it, as a result, the thermal resistance decreases and the heat transfer process is accelerated.
Keywords: Heat exchange, shell and tube device, internal and external surface, heat transfer coefficient, heat transfer coefficient, intensification method.